When a TV channel reinvents itself online: Post-broadcast consumption and content change at BBC Three - Thurman, Neil (Convergence: The International Journal of Research into New Media Technologies, 2021)
In February 2016, BBC Three became the first television (TV) channel in the world to close its linear broadcasting operation and instead prioritize offering its programming on demand, via the internet. Two Danish channels – both also youth-focused – followed in January 2020 for the same reason: budget cuts. Although the effects of ending offline distribution on the size and behaviour of newspaper and magazine audiences have been investigated, this article is the first to investigate the effects on a TV channel. The results show that BBC Three’s audience shrank by 60–70% after it closed its linear TV channel. The intensity with which the channel was viewed was even more sharply reduced: annual viewing minutes after the switch were 89% less than the channel achieved on linear TV before (and around 72% less if viewing of BBC Three-commissioned/acquired content on other BBC TV channels is included). The mix of programme genres consumed changed too, although further research is required to establish the part played by the change in distribution mechanism. This study furthers our understanding of media platform cessation by showing how change in the size of a media outlet’s audience after ending offline distribution may be affected by the proportion of its audience that consumes it exclusively offline before and how, irrespective of media platform, ending offline distribution seems to cause a sudden and substantial fall in the time spent with a media brand by its audience.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xMzU0ODU2NTIwOTY3Nzcz